Female foul language and foul female agents in pre-modern Portugal - Darlene Abreu-Ferreira (Ler História, 2017)
Through the examination of a number of archival sources and legislation from the late fourteenth to the eighteenth century, this study looks at the phenomenon of the female scold in pre-modern Portugal. Municipal records from certain regions indicate that local officials were confronted with disturbances caused by the scold, and royal ordinances outlined the jurisdiction for sentencing scolds. At both levels of government, the scold was persistently depicted as female. Moreover, a few elite male writers highlighted the problem with the quarrelsome woman, and offered their misogynist solutions to this perceived problem. The study concludes with an analysis of a decision rendered by Lisbon’s municipal council in the second half of the eighteenth century, a decision that aimed to abolish the office that dealt with scolding women.